2004
DOI: 10.1073/pnas.0404163101
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide molecular dissection of serotype M3 group A Streptococcus strains causing two epidemics of invasive infections

Abstract: Molecular factors that contribute to the emergence of new virulent bacterial subclones and epidemics are poorly understood. We hypothesized that analysis of a population-based strain sample of serotype M3 group A Streptococcus (GAS) recovered from patients with invasive infection by using genome-wide investigative methods would provide new insight into this fundamental infectious disease problem. Serotype M3 GAS strains (n ‫؍‬ 255) cultured from patients in Ontario, Canada, over 11 years and representing two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
115
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 44 publications
5
115
1
Order By: Relevance
“…Traditionally this "rheumatogenecity" has been considered to be a feature of strains belonging to certain M serotypes (the serotypes M3 and M18 have been related to ARF). Recent genome-wide analyses of group A streptococci have demonstrated that the heterogeneity in disease severity caused by group A streptococci is mediated by genetic variation in a signal transduction system that affects the expression of virulence factors (36,37). The combination of a susceptible host and a virulent group A Streptococcus may induce an exaggerated immune response, leading to valvular heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally this "rheumatogenecity" has been considered to be a feature of strains belonging to certain M serotypes (the serotypes M3 and M18 have been related to ARF). Recent genome-wide analyses of group A streptococci have demonstrated that the heterogeneity in disease severity caused by group A streptococci is mediated by genetic variation in a signal transduction system that affects the expression of virulence factors (36,37). The combination of a susceptible host and a virulent group A Streptococcus may induce an exaggerated immune response, leading to valvular heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of GAS diseases arises in part from the high diversity of GAS-mediated host-pathogen interactions in which virulence factors, GAS genome composition, prophage DNA, and plasticity of the GAS transcriptome play key roles (2,(61)(62)(63)(64). A major factor influencing the severity of GAS infections is also the genetic inventory of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, acquisition or loss of prophages, allelic variation in chromosomal genes, expansion of subclone populations, and introduction of new subclone variants were shown to contribute to peaks of infection and different infection types. 49 One finding from this study was particularly noteworthy and provided key insight into a potential mechanism accounting for clone emergence. Molecular genetic analysis, combined with immunological studies, implicated a 4-amino acid duplication in the extreme N-terminus of M protein as a factor contributing to rapid clone emergence.…”
Section: Genome-wide Dissection Of the Molecular Events Underlying Gamentioning
confidence: 95%
“…To test the hypothesis, 255 contemporary M3 strains obtained from an 11-year population-based surveillance study of invasive disease in Ontario, Canada, were analyzed. 49 Genetic diversity in these strains was investigated by several state-of-the-art methods, including DNA-DNA microarray and whole-genome PCR tiling. The core genome of all strains was identical in gene content.…”
Section: Genome-wide Dissection Of the Molecular Events Underlying Gamentioning
confidence: 99%
See 1 more Smart Citation